Analisis Lingkungan Kerja Terhadap Proses Bisnis pada Departemen Pengadaan Produksi Divisi Supply Chain di PT PAL Indonesia - Wahdatul Laili; Muhammad Alkirom Wildan (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
The physical work environment and non-physical work environment play an important role in supporting the productivity and operational efficiency of a company. This study aims to analyze work environment factors on business processes in the Production Procurement Department of the Supply Chain Division of PT PAL Indonesia with the challenges of adapting to changes in the workplace and the application of new technology, through several aspects of the work environment, such as work atmosphere, relationships between coworkers and relationships between subordinates and leaders. This research uses qualitative methods with data collection techniques through interviews and observations. The results showed that a conducive work atmosphere, effective communication between colleagues, and leadership support play an active and significant role in operational success. A good work environment improves performance and supports the achievement of company goals.